PHYTONEMATODES DURING PERIODS OF TOMATO DEVELOPMENT SPECIES COMPOSITION AND QUANTITATIVE DYNAMICS (Scientific journal of the Fergana State University, 2024)
Plant parasitic nematodes are recognized as one of the largest threats to crops worldwide. Nematodes, alone or in combination with other soil microorganisms, have been found to infect almost all parts of plants, including roots, stems, leaves, fruits and seeds. Determination of the species composition of nematodes was carried out according to generally accepted methods. This article notes that as a result of studying the dynamics of the species and number of phytonematodes under the conditions of tomato development in the Fergana region, 46 species of nematodes were identified in the plant and in the soil around the root.